2021
DOI: 10.1111/syen.12464
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the stink bug tribe Chlorocorini (Heteroptera, Pentatomidae) based on DNA and morphological data: the evolution of key phenotypic traits

Abstract: Pentatomidae is the third largest family of true bugs, comprising over 40 tribes. Few tribes have been studied in a phylogenetic context, and none of them have been examined using molecular data. Moreover, little is known about the evolution of key morphological characters widely used in taxonomic and phylogenetic studies at multiple levels. Here, we conduct a phylogenetic study of the tribe Chlorocorini (Pentatominae) combining 69 morphological characters and five DNA loci. We use the inferred phylogeny to re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…We obtained highly similar topology based on two different methods of two datasets. Our results are basically consistent with the traditional morphological classification and recent molecular studies ( Rider et al 2018 ; Chen et al 2021 ; Genevcius et al 2021 ). Eysarcorini and Strachiini are highly supported as monophyletic (1/100/1/100).…”
Section: Discussion and Conclusionsupporting
confidence: 93%
See 1 more Smart Citation
“…We obtained highly similar topology based on two different methods of two datasets. Our results are basically consistent with the traditional morphological classification and recent molecular studies ( Rider et al 2018 ; Chen et al 2021 ; Genevcius et al 2021 ). Eysarcorini and Strachiini are highly supported as monophyletic (1/100/1/100).…”
Section: Discussion and Conclusionsupporting
confidence: 93%
“…The data produced by Zhao et al (2019b) strongly supported Eurydema Laporte, 1833 within the tribe Strachiini and as a sister group with Nezara viridula (Linnaeus, 1758). Genevcius et al (2021) confirmed that the currently recognized Neotropical tribe Chlorocorini is not monophyletic based on DNA and morphological data. Roca-Cusachs et al (2022) rejected the currently accepted monophyletic nature of Pentatomidae , confirming that Serbaninae are a sister lineage of all remaining Pentatomidae , rather than members of Phloeidae as previously assumed.…”
Section: Introductionsupporting
confidence: 79%
“…The early classification of Pentatomidae subfamilies and tribes was mostly based on morphological data, Rider et al (2018) divided the family into ten subfamilies and provided an extensive description and discussion of the morphology of each subfamily and tribe within Pentatomidae. However, phenotypic plasticity was a major obstacle to morphological taxonomy (Barao et al, 2013;Sheikh, 2017;Sharif et al, 2020;Genevcius et al, 2021). With the widespread application of molecular technology, molecular data are more and more used in classification.…”
Section: Introductionmentioning
confidence: 99%
“…With the widespread application of molecular technology, molecular data are more and more used in classification. Genevcius et al (2021) made a preliminary discussion on the main phylogenetic relationships within Pentatomidae based on a combination of morphological and molecular data. In the most detailed analysis to date, which examined the phylogenetic relationships of the whole family of Pentatomidae based on mitochondrial (cox1 and 16S rRNA) and nuclear gene fragments (18S and 28S rRNA), Cyrtocorinae was excluded from ten subfamilies.…”
Section: Introductionmentioning
confidence: 99%
“…Anyway, recent DNA-based phylogenetic analyses suggest the current system of subfamilies and tribes of Pentatomidae as unsatisfactory and we may expect dramatic changes in its classification in the near future (e.g. [6][7][8][9][10]).…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%